2013
DOI: 10.1158/1535-7163.mct-12-1016-t
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Cells Refractory to Anti-VEGF Treatment Are Vulnerable to Glycolytic Blockade due to Persistent Impairment of Mitochondria

Abstract: Antiangiogenesis therapy has shed new light on cancer treatment, but its effectiveness, especially for overall patient survival, is still controversial. Here, we show that antiangiogenesis treatment causes a persistent suppression of mitochondria biogenesis in colorectal cancer cells, which renders them more sensitive to glycolytic blockade therapy. We first analyzed bevacizumab-resistant colon cancer xenografts by twodimensional Blue Native/SDS-PAGE and found a serious and persistent loss of mitochondrial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
2
32
1
Order By: Relevance
“…These models yielded important distinct findings compared with previous studies, such as our finding of unchanged number of mitochondria in resistant versus sensitive xenografts, a finding that contrasts with reports of decreased mitochondria in bevacizumab-treated xenografts (17,18). These findings suggest that a recovery of mitochondrial mass lost during initial treatment occurs during the evolution of resistance to antiangiogenic therapy despite persistent functional impairment of these mitochondria.…”
Section: Discussioncontrasting
confidence: 52%
“…These models yielded important distinct findings compared with previous studies, such as our finding of unchanged number of mitochondria in resistant versus sensitive xenografts, a finding that contrasts with reports of decreased mitochondria in bevacizumab-treated xenografts (17,18). These findings suggest that a recovery of mitochondrial mass lost during initial treatment occurs during the evolution of resistance to antiangiogenic therapy despite persistent functional impairment of these mitochondria.…”
Section: Discussioncontrasting
confidence: 52%
“…In this respect, it has been reported that glucose deprivation provides a strong selection for activated oncogenes, such as KRAS (42). Moreover, Xu and colleagues recently described mitochondrial defects in ex vivo cultures of LoVo cells from bevacizumab-treated tumors (43), and we also found reduced mitochondrial mass and decreased expression of NDUFS1, a component of respiratory complex I, in ex vivo cultures of bevacizumab-treated IGROV-1 cells (Supplementary Fig. S5).…”
Section: Discussionsupporting
confidence: 73%
“…As a result, cancer cells turn more to non-oxidative metabolism, which could contribute to the selection of resistant cancer clones [21]. A compelling observation is that antiangiogenic treatment can induce persistent metabolic changes in cancer cells (i.e., suppression of mitochondrial biogenesis and hyperactive glycolysis) [22]. Whether this reflects epigenetic reprogramming of metabolism with long-lasting effects is unknown but certainly deserves investigation.…”
Section: Why Target Endothelial Metabolism?mentioning
confidence: 99%